Frequency and Risk Factors of Biliary Complications after Living Donor Liver Transplant: A Case-Control Study - Tariq Azim, Mansoor; Rashid, Sohail; Saleem, Muhammad Asad; Mansoor, Eisha; Zafar, Hiba (Pakistan Armed Forces Medical Journal, 2026)
Objective: To identify the frequency and risk factors of biliary complications in patients undergoing living donor liver transplantation (LDLT) at a single national referral center. Study Design: Case-control study. Place and Duration of Study: Pakistan Kidney and Liver Institute and Research Centre, Lahore Pakistan, from Mar to Nov 2024. Methodology: Out of 500 patients who underwent LDLT, the ones who developed biliary complications (stricture, leak, or stones) were selected as cases (Group-A, n=125) while controls (Group-B, n=375) were the recipients who did not develop any biliary complications. Data on donor/recipient demographics, surgical details, and clinical variables was collected from the institutional electronic medical records. Chi square test was used to find association between the risk factors and biliary complications. Results: Biliary complications occurred in 25% (n=125) of recipients. Anastomotic biliary stricture was the most common complication (100%), followed by stone formation (26.4%) and bile leak (3.4%). A statistically significant association was found between the number of ducts and frequency of biliary complications (OR= 1.7, 95%CI=1.14 - 2.56, p-value =0.01). Hence, the cases had 70% greater odds of having double ducts as compared to the controls. Conclusion: In this study, 25% of LDLT recipients developed biliary complications, predominantly strictures. A statistically significant association was found between the number of ducts and biliary complications. These findings underscore the need for tailored surgical and postoperative strategies in patients with multiple bile ducts.